2006
DOI: 10.1063/1.2171485
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and dilution in implanted MnxGe1−x alloys

Abstract: The structural and electronic properties of Mn x Ge 1−x alloys ͑x ഛ 0.15͒ fabricated by ion implantation are investigated by means of x-ray diffraction and synchrotron radiation photoemission spectroscopy. The diffraction patterns point to the presence of ferromagnetic Mn 5 Ge 3 nanoparticles; however, valence band spectra, interpreted by means of accurate ab initio calculations including Hubbard-like correlations, show clear fingerprints of an effective substitutional Mn dilution in the Ge semiconducting host. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 18 publications
4
49
1
2
Order By: Relevance
“…The situation is particularly serious in the case of small band-gap semiconductors (such as Ge) which are described as metals in LDA/GGA, thus producing an overestimated hybridization among the valence and conduction Ge states and Mn-d states. The physics of localized d states can be partially described using a DFT+U formalism, which introduces a local correction U to recover the proper position of the Mn-d states [6]. However, in Ge, the accurate electronic properties are not completely recovered: e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is particularly serious in the case of small band-gap semiconductors (such as Ge) which are described as metals in LDA/GGA, thus producing an overestimated hybridization among the valence and conduction Ge states and Mn-d states. The physics of localized d states can be partially described using a DFT+U formalism, which introduces a local correction U to recover the proper position of the Mn-d states [6]. However, in Ge, the accurate electronic properties are not completely recovered: e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison among different TM as dopants for Ge revealed that Mn is indeed the best candidate, since it grants holes that can mediate FM coupling as well as relatively high moments [4]. While appealing from the theoretical point of view, the growth of an Mn x Ge 1−x alloy with an appreciably homogeneous dilution of Mn [5] in the semiconducting host was found to be a challenge: the formation of energetically competing nanoscale-sized phases [6,7] (in particular showing the hexagonal crystallographic phase Mn 5 Ge 3 [8]) occurs even under small concentrations of Mn and on a wide range of growth conditions (in terms of substrate temperatures, growth rates, etc). More recently, nanoscale spinodal decomposition was suggested to occur in Mn-doped Ge samples, with the formation of Mn-rich nanocolumns showing a high FM ordering temperature (∼400 K) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, comparison of valence band spectra with ab initio calculations indicated effective substitutional Mn dilution, even after high fluence ion implantation. 10 Besides these experimental studies, several ab initio calculations have been performed to determine the heat of formation of Mn on different lattice sites, all of which indicated that Mn prefers the S site to the tetrahedral ͑T͒ or hexagonal ͑H͒ interstitial site. [11][12][13] Here, we present an electron emission channeling ͑EC͒ on-line experiment in combination with ab initio calculations, in order to determine the lattice location of implanted diluted Mn atoms in Ge in a direct way.…”
mentioning
confidence: 99%